Pemanfaatan Program Power Point Sebagai Media Untuk Meningkatkan Motivasi Belajar Sejarah Peserta Didik Kelas XII IPS SMA Negeri 12 Pekanbaru - Nelwita Nelwita (Lembaga penelitian dan pengabdian kepada masyrakat, 2022)
AbstractThis research is motivated by the problem of learning history which is considered difficult and boring so it results in low learning outcomes. One of the factors that cause students to experience delays in integrating teaching materials is not using tools (media) in learning, in addition to using content that is not on target and not following the current social context. This research aims to improve and improve the quality of history learning and to help empower teachers in solving history learning problems at SMA Negeri 12 Pekanbaru. This research method uses Classroom Action Research in class XII IPS 1 SMA Negeri 12 Pekanbaru. Based on the results of the study it was concluded that the use of powerpoint media can increase learning motivation and learning outcomes of students in SMA Negeri 12 PekanbaruTRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//